THE IMPACT OF KNOWLEDGE, BELIEF, AND CONVENIENCE OF USE ON CONSUMER INTEREST IN USING SERVICES M-BANKING - Sri Mulyani; Retno Wulansari (JURNAL PROFIT, 2025)
The aim of this research was to find out the impact of knowledge, belief, and interest of use on Consumer interest in using M-Banking services. This study uses a quantitative method. The population in this study was 3,200 Consumers, for sample calculation using the Slovin formula random sampling method with the number of respondents being 97 Consumers. The data analysis method in this study used multiple linear regression in the SPSS 23 For Windows application. The t-test findings show that the knowledge factor has an effect on Consumer interest in using M-Banking services. While the belief factor does not affect Consumer interest in using M-Banking services. The convinence factor affects Consumer interest in using M-Banking. The factors of knowledge, belief and convinence of use simultaneously affect Consumer interest in using M-Banking services at Bank Syariah KCP Malang Pakis Kembar. From the finding of the percentage of determination (R2) given by the factors of knowledge, belief and ease of use on Consumer interest, it contributed 58.8% and the rest was influenced by other factors not included in this study of 41.2%.